Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair

Shape-selective oriented cerium oxide nanocrystals permit assessment of the effect of the exposed facets on catalytic activity and oxygen storage capacity - Sreeremya, Thadathil S.; Krishnan, Asha; Remani, Kottayilpadi C.; Patil, Kashinath R.; Brougham, Dermot F.; Ghosh, Swapankumar (ACS Applied Materials & Interfaces, 2015)
The catalytic performance of a range of nanocrystalline CeO2 samples, prepared to have different morphologies, was measured using two accepted indicators; oxygen storage and diesel soot combustion. The same powders were characterized hi detail by HR-TEM, XRD, XPS, and Raman methods. The study demonstrates that activity is determined by the relative fraction of the active crystallographic planes, not by the specific surface area of the powders. The physical study is a step toward quantitative evaluation of the relative contribution to activity of the different facets. The synthetic protocol permits fabrication of CeO2 nanostructures with preferentially grown active planes, and therefore has potential in developing catalytic applications and in nanocompositing.
Keywords: ceria; chemical activities; crystal facets; nanocrystals; texture coefficient